PERBANDINGAN PENDEKATAN RME DAN SAINTIFIK BERBANTUAN ADOBE FLASH CS5 TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS DAN SELF-EFFICACY SISWA - Rahmawati, Novi; Maulana, M.; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2019)
This research aims to know the influence, get a comparison between both approaches (RME and saintifik approachs), and knowing the correlation of these two goals. The research method used true experimental design, pretest-posttest control group design. The population is all second grade students in Sumedang. The second grade student’s in the experimental group I (Panyingkiran III Elementary School) and group II (Sukamaju Elementary School) as the research samples. The results of this research are: 1) Learning mathematics using the RME and a scientific approach with adobe flash CS5 has a influence significantly on mathematics comprehention ability (cognitive goals) and student’s self-efficacy (affective goals) of fraction subject matter. 2) The difference is in improving cognitive and affective goals of fraction subject matter, RME is better than scientific approach. 3) There is a positive correlation between the mathematics comprehention ability and students self-efficacy in learning mathematics using RME and a scientific approach.